The new EU migration and asylum package: Breakthrough or admission of defeat? - Steffen Angenendt; Nadine Biehler; Raphael Bossong; David Kipp; Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2020)
On 23 September 2020, the European Commission presented its long-awaited draft of a new migration and asylum package to overcome the protracted blockade in this policy area. Central elements are the planned preliminary examinations of asylum applications at the external borders of the European Union (EU) and a new division of labour among the member states, which in the future will have the choice between accepting asylum seekers and returning those who have been rejected. The risk of human rights violations inherent in these suggestions is immense. However, since this also applies to the status quo - as the situation on the Greek islands shows - the pros and cons of the reform proposal must be carefully weighed up. Support for the reform package can only be justified if the combination of restrictive and protection-oriented elements, as intended by the Commission, is maintained in the intergovernmental negotiations.
Keywords: 320